The Outlook for Food Security in Razavi Khorasan Province (2024-2033) from the Perspective of Crop Products (Based on Water Capacity) - A Keshavarz; A Zarea Feizabadi; F Yaghoubi (پژوهشهای زراعی ایران)
IntroductionThe food security of any country is directly dependent on the production of its agricultural sector, and any disruption in the production process of this sector can directly threaten the food, social, economic and even political security of the country. In other words, the agricultural sector, as a productive sector, is responsible for eliminating and reducing poverty and ensuring food security. In the current situation, due to the ever-increasing demand and the significant growth of the population, the indiscriminate and incorrect exploitation of limited and non-renewable resources and reserves, as well as the occurrence of challenges such as climate change, ensuring food security and maintaining it, are of great importance. The purpose of this study was to investigate the availability of crop products in Razavi Khorasan province in two horizons of 5 and 10 years under two scenarios of full irrigation and deficit irrigation in accordance with the water capacity of the province and to provide appropriate solutions.Materials and MethodsThis study was carried out in Razavi Khorasan province for the time period of 2017-2020 as the baseline and 2024-2028 and 2024-2033 as 5- and 10-year horizons, respectively. The information needed for this study was obtained through documentary and library studies, generally by referring to the official centers that publish the country's information and published documents (especially the Ministry of Agriculture and the Agricultural Jihad Organization of Razavi Khorasan province), field information and also by completing the questionnaire from national experts and holding meetings with stakeholders and experts. Finally, the changes in the harvested area, yield, production, volume of water consumption and water productivity of important irrigated (under two scenarios of full irrigation and deficit irrigation) and rainfed crops, as well as indicators of per-capita consumption, production, demand, trade, and the percentage of self-reliance of these crops were estimated and evaluated in 5- and 10-year horizons compared to the baseline (2017-2020).Results and DiscussionAccording to the results, if the objectives of this study are achieved, the crop water requirement and total water consumption will decrease across both scenarios and time horizons, while water productivity will improve compared to the baseline. In the projected horizon periods, the yield of both irrigated and rainfed crops will increase compared to the baseline. The harvested area of irrigated crops will decrease, while the harvested area of rainfed crops will expand. However, under deficit irrigation conditions, the production of both rainfed and irrigated crops will rise, whereas irrigated crop production under full irrigation conditions will decline, aligning with water balance objectives. These changes will occur mainly due to the increase in the harvested area and production of fodder sorghum, silage, fodder beet, and autumn beet and the decrease in the harvest area and production of alfalfa, irrigated vegetable crops, and spring beet. Despite the increase in the demand of important crop products of the province in 5- and 10-year horizons by 10 and 17% (considering population growth and improvement in per-capita consumption), respectively, the amount of production of these products will decrease by 2% in 5-year horizon and increase by only 1% in 10-year horizon. Therefore, it is predicted that the self-reliance of the province's total production will decrease from 74% in the baseline to 68% and 67% in the 5- and 10-year horizons, respectively. In order to achieve the results of this study, solutions such as paying attention to aquifers and watersheds, cultivation of fallow lands, increasing soil organic matter, real development of conservation agriculture, development of autumn and waiting planting, development of alternative crops (especially fodder crops), and provision, production, distribution, and consumption of inputs in a timely and appropriate manner are suggested.ConclusionIn total, the results of this research showed that the proposed production pattern for crops in Razavi Khorasan province and 5 and 10-year horizons will be consistent with the water capacity of the province, especially in the deficit irrigation scenario. However, the realization of the results of this study requires the categories of "research", "technology", "education and empowerment", and "promotion of achievements".